Multi-beam single-photon LiDAR with hybrid multiplexing in wavelength and time. (January 2022) - Wu, Di; Zheng, Tianxiang; Wang, Linli; Chen, Xiuliang; Yang, Lei; Li, Zhaohui; Wu, Guang
Highlights: Multi-beam single-photon LiDAR at 1550 nm. Hybrid multiplexing technology of wavelength and time based on FPGA. Coaxial detection optical path of single-beam transceiver and multi-beam detection based on a blazed grating. Suitable for LiDAR measurement in the field of human eye safety, such as vehicle LiDAR. Abstract: We report a multi-beam single-photon light detection and ranging (LiDAR) in eye-safe band at 1.5 µm with hybrid multiplexing in wavelength and time. 16 independent laser diodes with equal frequency spacing in dense wavelength division multiplexing (DWDM) were combined with a blazed grating to generate multi-beam dispersing with equal angle in space as the LiDAR laser source. Meanwhile, time division multiplexing (TDM) was applied on the 16 laser diodes as well. A single-pixel single-photon detector (SP-SPD) was used to detect the echo photon signal of all laser beams by TDM. In this way, we constituted a compact optical system without multi-beam transceiver alignment. The LiDAR system was simple and robust with this hybrid multiplexing technology. An outdoor photon-counting imaging within 75-m range was achieved, with the laser power lower than 1/10 of the human eye safety threshold. It has high application potential in the field of automatic driving with strict eye safety requirements.